Faktor-Faktor yang Mempengaruhi Return Saham Syariah Perusahaan Sub Sektor Tourism, Restaurant, and Hotel - Harivani Nurwiyati; Diharpi Herli Setyowati; Destian Arshad Darulmalshah Tamara (Journal of Applied Islamic Economics and Finance, 2021)
The purpose of this study is to analyze the influence of current ratio, debt to equity ratio, return on equity, and inflation rate to return stock of sub sector tourism, restaurant, and hotel companies listed on Indonesia Sharia Stock Index (ISSI). The population used is sharia service sector companies listed on ISSI. The sample is determined using purposive sampling. This research is a descriptive study with a quantitative approach. The data analysis method used is a panel data regression. Based on the results with a significance level of 5%, this study shows: Current ratio, Debt to equity ratio, and Inflation rate partially have No. significant effect to return stock. Return on equity partially has asignificant negative effect to return stock. Current ratio, debt to equity ratio, return on equity, inflation rate simultaneously have a significant effect on stock returns.